Molecular and biochemical responses in the midgut of the silkworm, Bombyx mori, infected with Nosema bombycis - Zhi Li; Yu Wang; Linling Wang; Zeyang Zhou (Parasites & Vectors, 2018)
Abstract Background Microsporidia are a group of eukaryotic intracellular parasites that infect almost all vertebrates and invertebrates. However, there is little information available of how microsporidia obtain nutrients and energy from host cells. The purpose of this study was to investigate the energy and material requirements of Nosema bombycis for the invasion procedure through analyzing the global variation of the gene expression, protein abundance, fatty acids level and ATP flux induced by the microsporidia N. bombycis infection in the midgut of the silkworm Bombyx mori. Methods A suppression subtractive hybridization (SSH) and quantitative real-time PCR (qPCR) analysis were performed to identify the genes upregulated in the midgut of B. mori 48 h following N. bombycis infection. Gene Ontology (GO) and the Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses were used to annotate and summarize the differentially expressed genes, according to the categories ‘molecular function’, ‘cellular component’ and ‘biological process’. To evaluate the nutrition material and energy costs in B.mori infected by N. bombycis, biochemical analysis was performed to determine the variation of protein abundance, fatty acid levels and ATP flux with or without the microsporidia N. bombycis infection in the midgut of the silkworm B. mori. Results A total of 744 clones were obtained, 288 clones were randomly selected for sequencing, and 110 unigenes were generated. Amongst these, 49.21%, 30.16% and 14.29% genes were involved in 19 molecular functions, 19 biological processes and nine cellular components, respectively. A total of 11 oxidative phosphorylation- and eight proton-coupled ATP synthesis-related genes were upregulated. Seven protein degradation-, three fat degradation-related genes were upregulated, and no genes related to the de novo synthesis of amino acids and fatty acids were significantly upregulated. The data from the biochemical analysis showed the contents of total protein and ATP of B. mori midgut tissues decreased significantly, whereas the fatty acid content did not significantly change after four days of N. bombycis infection. Microsporidia N. bombycis infection upregulated the expression level of genes involved in host ATP synthesis, protein and fat degradation, which eventually causes the obvious decline of protein content and ATP synthesis in the host midgut, whereas the fatty acids content did not change significantly. Conclusions This study suggested to some extent that N. bombycis invasion can activate the host protein degradation and accelerate the production of host ATP. Microsporidia of N. bombycis show preference for proteins rather than fatty acids from the host to ensure the material preparation required by their parasitic life-cycle. Requirements of N. bombycis for energy were also mainly dependent on the host ATP production. This study provides a new data that may help our understanding of the molecular mechanisms of obtaining energy and nutrients from the host by the microsporidium N. bombycis.